Skidelsky's Keynes: A review essay - David Laidler (The University of Western Ontario, Department of Economics, 2001)
[...] It would not be fair to Skidelsky to pile up a longer list of infelicities of this sort. He is primarily an historian who has had to learn economics more or less from scratch in order to write a biography of a great economist who was much else besides. It is unreasonable to expect him to have turned himself into a full-time historian of economic thought at the same time. His work seems to me to be a great success inasmuch as it is judged as a portrait of an extraordinary human being in his social milieu. Furthermore, the representation of Keynes's own economics as a part of that portrait is by and large accurate. As is so often the case with portraits of individuals, however, the background is highly stylised, designed to enhance the appearance of the sitter, and symbolise his accomplishments to the viewer, rather than to provide an accurate topography of the intellectual landscape which he inhabited. For those of us who are concerned with the biographies of economic ideas as well as of economists, Skidelsky's uncertain treatment of the economic thought of Keynes's predecessors and contemporaries matters more than it will to general readers, but it is to be hoped that some of these problems will have been addressed when the promised single volume abridgement of this biography appears.
Keywords: 330